Fractional-order dynamics of human papillomavirus - Zafar, Zain Ul Abadin; Hussain, M. T.; İnç, Mustafa; Baleanu, Dumitru; Almohsen, Bandar; Oke, Abayomi S.; Javed, Shumaila (Elsevier, 2022)
Human papillomavirus (HPV) is a reproductive tract infection common to sexually active human. Many of the low-risk HPV infections clear up without any medications but the High-risk HPV-related diseases can remain in the body for a long time. Most of the cases of cervical cancers and other genital cancers are consequences of HPVrelated diseases. As HPV-related diseases are on the increase and controlling the spread is becoming difficult, this present study explores the influence of vaccination on the spread of the diseases. A fractional order mathematical model that captures different HPV risk level is developed in this study. The basic reproduction ratio is obtained for the fractional order model and a locally asymptomatically stable disease-free equilibrium is shown to exist. A comprehensive analysis of the effect of vaccination efficacy and rate of vaccination is carried out and the results indicate that the spread of HPV infection can be mitigated by vaccination.
Keywords: Human papillomavirus (HPV); Next-generation method; Low -high risk type vaccination; Basic reproduction ratio; Cervical cancer